JENIS-JENIS KATAK (AMPHIBI: ANURA) DI DESA KEPENUHAN HULU KECAMATAN KEPENUHAN HULU KABUPATEN ROKAN HULU PROVINSI RIAU - Winata, Egi Yuda (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
Study on diversity frog (Amphibians: Anura) in Desa Kepenuhan Hulu Kecamatan Kepenuhan Hulu Kabupaten Rokan Hulu, Riau has been conducted from November to Desember 2015 by using visual encounter survay (capture directly to the survey) by the sampling technique samples by random sampling. Samples were collected with two repetitions at each station. The results, isÂ four family, six genera and ten species are Rana erythraea, R. baramica, R. nicobariensis, R. hosii, Fejervarya limnocharis, F. cancrivora, Limnonectes paramacrodon, Leptobrachium hasseltii, Rhacophorus javanus and Kaloula baleata